Rationale and methods of an observational study to support the design of a nationwide surgical registry: the MIDAS study (Swiss Medical Weekly, 2018)
BACKGROUND Surgical registries are becoming increasingly popular. In addition, Swiss legislation requires data on therapeutic outcome quality. The Swiss Association of Surgeons (Schweizerische Gesellschaft Chirurgie, SGC-SCC) has already agreed on a first minimum data set. However, in the long run the scope and content of the registry should be evidence-based and not only accepted by professional stakeholders. The MIDAS study aims at providing such evidence for the example population of patients undergoing emergency or elective hip surgery. Five relevant aspects are considered: (1) choice of instruments for assessing health related quality of life (HRQoL); (2) optimal time-point for assessment; (3) use of proxy assessments; (4) choice of pre-surgery risk factors; and (5) assessment of peri- and postoperative variables. METHODS MIDAS is a longitudinal observational multicentre study. All patients suffering from a femoral neck fracture or from arthritis of the hip joint with an indication for prosthetic joint replacement surgery will be offered participation. The study is based on a combination of routine data from clinical standard practice with specifically documented data to be reported by the treating clinician and data to be collected in cooperation with the patient – in particular patient-reported outcome measures (PROMs). The latter include the Health Utility Index Mark 3 (HUI3) and Euro-Qol-5D (EQ-5D) as generic instruments, Hip Disability and Osteoarthritis Outcome Score (HOOS) as a disease specific instrument for the assessment of HRQoL, and two performance-based functional tests. Data will be collected at baseline, during hospitalisation/at discharge and at three routine follow-up visits. All patients will be asked to name a person for assessing proxy-perceived HRQoL. DISCUSSION To the best of our knowledge, this is the first study explicitly addressing questions about the design of a national surgical registry in an empirical manner. The study aims at providing a scientific base for decisions regarding scope and content of a potential national Swiss surgical registry. We designed a pragmatic study to envision data collection in a national registry with the option of specifying isolated research questions of interest. One focus of the study is the use of PROMs, and we hope that our study and their results will inspire also other surgical registries to take this important step forward. Trial registration Registered at the “Deutsches Register Klinischer Studien (DRKS)”, the German Clinical Trials Registry, since this registry meets the scope and methodology of the proposed study. Registration no.: DRKS00012991